Prevalence of an association between coeliac disease and vitiligo - Henker, J.; Hartmann, Arndt (Hautarzt, 2019)
Coeliac disease and vitiligo are immune-mediated disorders that are often associated with other immune-mediated disorders. In a prospective study we included 174 patients with vitiligo between the ages of 3 and 79 years (mean 38.2 years) to investigate whether there is an increased risk for coeliac disease in patients with vitiligo. We determined immunoglobulin A and IgA- and IgG-antibodies against tissue transglutaminase, while also optionally measuring blood count, ferritin, and endomysial-IgA-antibodies. In 3 of 174 (1.7%) vitiligo patients, coeliac disease was diagnosed serologically and by duodenal biopsy. Assuming a coeliac disease prevalence of less than 0.0033%, the incidence is statistically significant. In two other patients with vitiligo, coeliac disease was already known and confirmed with biopsy. If these two patients are included in the calculation, 2.8% (5 von 176) of vitiligo patients have coeliac disease. This value is statistically significant even with a higher coeliac disease prevalence of 0.01. Thus, it is recommended that celiac-disease-specific antibodies also be determined during routine blood workup in vitiligo patients. In case of positive results, a gastroduodenoscopy with biopsy of the small intestine is recommended for diagnosis confirmation. If celiac disease is unlikely, a trial of gluten-free diet for a specific time should nevertheless be discussed with individuals affected by vitiligo because repigmentation appears possible.
CRIS-Team WoS Importer:2019-10-18